2019
DOI: 10.1177/0734242x19862603
|View full text |Cite
|
Sign up to set email alerts
|

Fate of nano titanium dioxide during combustion of engineered nanomaterial-containing waste in a municipal solid waste incineration plant

Abstract: The market for products containing engineered nanomaterial (ENM) is constantly expanding. At the end of their lifecycle, a significant fraction of the products will be disposed as ENM-containing waste in thermal treatment plants. Up to now there are still uncertainties on the fate and behaviour of ENM during waste incineration. In our investigations, nano titanium dioxide (nTiO2) was selected as an example for ENM, because of its high amount in consumer products and its relevance to the ENM-containing waste st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The selective accumulation of ENPs in bottom ash has been previously observed for TiO 2 -NPs. 13,24 The excellent recovery of Au in the fly and bottom ash and the agreement between the calculated and ideal EFs indicated that during the incineration experiment, all relevant Au mass flows were collected, i.e. Au volatilization was insignificant.…”
Section: Experiments A: Characterization Of Enp Spiked Samplesmentioning
confidence: 72%
See 1 more Smart Citation
“…The selective accumulation of ENPs in bottom ash has been previously observed for TiO 2 -NPs. 13,24 The excellent recovery of Au in the fly and bottom ash and the agreement between the calculated and ideal EFs indicated that during the incineration experiment, all relevant Au mass flows were collected, i.e. Au volatilization was insignificant.…”
Section: Experiments A: Characterization Of Enp Spiked Samplesmentioning
confidence: 72%
“…In the first fraction, the Ca concentration and pH were in equilibrium with Ca(OH) 2 (SI = 0.03), but the SI already dropped to −0.75 in the second fraction and continuously decreased. The elevated Ca concentrations (7000 and 12 000 mg kg −1 Ca in sludge and fly ash, respectively) can be traced back to the hard water (French degree hardness (fH) = [22][23][24][25] in the catchment of the WWTP in La Chaux-de-Fonds originating from the limestone rich lithology of the Jurassic mountain range in the western part of Switzerland. As observed in experiment A, the release of particulate Au was independent of the Ca concentration.…”
Section: Experiments B and C: Characterization Of Fly Ash Samplesmentioning
confidence: 99%
“…As a basis for the formulation of Hombikat UV 100 WP, nTiO 2 , in the form of the product Hombikat UV 100 with a primary particles size of <10 nm, was employed. Further information can be found in Börner et al [ 16 ] and Oischinger et al [ 17 ]. The application of Hombikat UV 100 WP lies mainly in the photocatalytic area, as the nTiO 2 is present in the anatase modification.…”
Section: Methodsmentioning
confidence: 99%
“…Most of these studies occurred at laboratory-scale (Cernuschi et al 2019;Ounoughene et al 2015Ounoughene et al , 2019Pourchez et al 2018;Baumann et al 2017;Buonanno and Morawska 2015;Massari et al 2014;Buha et al 2014;Marr 2013, Vejerano et al 2014;Derrough et al 2013;Cernuschi et al 2012;Mueller et al 2012;Buonanno, Ficco, and Stabile 2009), making some of their conclusions somewhat study specific as the full complexity involved in waste incineration was not taken into account. For the large-scale studies (Oischinger et al 2019; Baran and Quicker 2017;B€ orner et al 2016;Lang et al 2015;Walser et al 2012), the majority of the NMs ended up in the bottom ash while some fractions of the NMs were detected in the fly ash. These conclusions were also partly supported by some of the lab-scale studies.…”
Section: Introductionmentioning
confidence: 99%